Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1432-1033.1989.tb14920.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐responsive S6 kinase

Abstract: Many cell lines respond to mitogenic stimuli (serum, growth factors) with rapid phosphorylation of the ribosomal protein S6 at several serine sites. We have tried to identify the protein kinase(s) mediating this effect of growth stimuli. Examining post-DEAE chromatography fractions of S49 kin ~ cell extracts, we could detect a highly active effector-independent S6 kinase with specificity for serine residues. The study was extended to the presumably homologous human enzyme, using HeLa S3 cells as model system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…Phosphoamino acid analysis revealed that S6 was phosphorylated exclusively at the serine residues (Fig. 3b), a result consistent with all past reports on the subject (34).…”
Section: Comparison Of the Manduca S6 Sequence To That Of Othersupporting
confidence: 91%
“…Phosphoamino acid analysis revealed that S6 was phosphorylated exclusively at the serine residues (Fig. 3b), a result consistent with all past reports on the subject (34).…”
Section: Comparison Of the Manduca S6 Sequence To That Of Othersupporting
confidence: 91%